The knowledge of chromosomal sex is important for large-scale analysis of gene expression - Lykhenko, O.K.; Obolenskaya, M.Yu. (Reports of the National Academy of Sciences of Ukraine, 2021)
The aim of the study was to determine the sex of the fetus in gene expression data lacking this information using expression of the Y-linked genes, and to elucidate the difference between sex-chromosomal-linked gene expression between placental samples with XX and XY genotypes during pregnacy. We have detected 27 differentially expressed sex-chromosomes-linked genes. We have shown that, in most cases, the expression of genes from X-chromosomes in pregnancy carrying baby girls is higher than in pregnancy carrying baby boys, but there are exceptions to this pattern, which must be taken into account in large-scale studies of gene expression. The nature of the difference in gene expression during pregnancy carrying baby girls and boys (positive or ne gative difference) persists during pregnancy, but the magnitude of the difference may remain unchanged or decrease from the first to the third trimester. Taking sex dimorphism into account when analyzing large-scale gene expression data between trimesters of pregnancy increases the number of differentially expressed genes, which improves the informative value of the study and is important for elucidating the pathogenesis of pregnancy complications associated with placental dysfunction.